Transcription of DNA from the 70S RNA of Rous Sarcoma Virus II. Structure of a 4S RNA Primer - Faras, A. J. (1974)
The 70S RNA of Rous sarcoma virus contains 4S RNAs which serve as primers for the initiation of DNA synthesis in vitro by the RNA-directed DNA polymerase of the virus. We purified these primers in three different ways—by isolation of the covalent complex between primer and nascent DNA, by differential melting of the 70S RNA, and by two-dimensional electrophoresis in polyacrylamide gels. The 4S RNAs purified by these procedures were homogeneous and possessed very similar if not identical nucleotide compositions and sequences. The RNAs were approximately 75 nucleotides long, had pG at the 5′ terminus and CpCpA(OH) at the 3′ terminus, and contained a number of minor nucleotides characteristic of tRNA. In contrast to most tRNA's, the primer lacked rTp and contained Gp (Ψp, Ψp, Cp) Gp (possibly in place of the characteristic sequence GprTpΨpCpGp). At least 50% of the 4S primers available on 70S RNA were utilized in a standard polymerase reaction in vitro.